The Relationship between Reproductive Hormones and Metabolic Parameters in Women with Polycystic Ovary Syndrome - Ahmed, Hind Sh.; Abbas, Ahsan K. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Polycystic ovarian syndrome (PCOS) is a condition associated with chronic anovulation, and androgen excess. Clinically, PCOS women usually presents with menstrual irregularities, infertility, and hirsutism. Women with this syndrome are at increased risk of metabolic syndrome (MS).Patients and Methods: This study was conducted during the period from March 2013 until the end of September 2013. A total of 50 PCOS women were studied   (25 PCOS women with MS and 25 PCOS women without MS) with an age ranged from (35-45) years. Women with PCOS were referred to Medical City Hospital in Baghdad and compared with 25 healthy women as control group. Serum luteinizing hormone (LH), follicle stimulating hormone (FSH), prolactin, progesterone, testosterone, fasting serum glucose (FSG), serum triacylglycerol (TAG), and high density lipoprotein cholesterol (HDL-C) were measured for each individuals.Objective: To study the characteristics of the MS in women with PCOS.Results:  Means of FSG, TAG, LH, prolactin, progesterone, testosterone levels, and LH/FSH ratio were significantly elevated in PCOS women than in the control group, while serum HDL-C levels were significantly lowered in PCOS women than in the control. There was a significant increase in FSG and TAG in PCOS women with MS as compared to PCOS women without MS, (P=0.0001). While, there was a significant decrease in serum HDL-C in PCOS women with MS as compared to PCOS women without MS. No significant differences were found in LH, FSH, prolactin, progesterone, testosterone, LH/FSH ratio, day of menstrual cycle, and duration of infertility between PCOS women with and without MS.                                                                       Conclusions: The present study showed that PCOS women with MS had abnormalities in hormonal and lipid profile.